Geometric Modeling and Kinematic Simulation of Hand Prosthesis for Adult Patients with Transradial Amputation - Zavala Molina, Diego Alonso (2023)
Background: Transradial amputation, which involves the loss of the upper limb below the elbow, is a reality that deeply affects people's lives. Objective: The research demonstrated the objective of modeling and simulating the movement of the fingers of a prosthesis for adult patients with transradial amputation, to increase their quality of life by allowing them to carry out specific daily activities more easily. Methodology: The morphological analysis and CAD design of the hand was carried out using as a model the hand of a volunteer adult patient with right transradial amputation. Likewise, the CAD design of the 2 DOF thumb was detailed using the SolidWorks Professional engineering software. Then kinematic modeling of the fingers of the hand was carried out using the Denavit – Hartenberg algorithm and the movements of the fingers were simulated using the Matlab engineering software. Results: The initial and final positions of the end of the fingers of the hand, as well as the trajectories during the simulation of hand closure, were obtained. Conclusions: Taking measurements from a patient maximizes the possibility of implementing a functional prototype. Kinematic modeling allows simulating the trajectories of the fingers of the hand with the Matlab software.